Optimizing the Precision Oncology Workflow at a Public Safety-Net Cancer Center - Diasti, Kevin; Yu, Peter; Varma, Gaurav; Bhatt, Ahan; Wu, Jennifer (British Journal of Healthcare and Medical Research, 2025)
Background: Comprehensive tumor molecular profiling using next-generation sequencing (NGS) enables personalized cancer treatment and is standard of care in the management of advanced solid malignancies. Given challenges with efficient implementation of NGS testing in safety-net health care settings, we evaluated the tissue NGS workflow at our facility and investigated the impact of a targeted specimen courier service intervention. Methods: We constructed a NGS workflow process map to identify key stakeholders and potential sources of delays. 26 clinicians were surveyed regarding time spent placing orders, reliance on a process guide sheet, and adherence to key steps in the ordering process. Utilization and process data from 2019-2022 was obtained from our NGS vendor. Time from order placement to result report [Turn Around Time; (TAT)] was the primary process measure; secondary measures were time from order placement to specimen receipt by the vendor [Order to Specimen (OTS)] and time from specimen receipt to reporting of results [Specimen to Report (STR)]. Medians for TAT, OTS, and STR were compared over 3-month intervals, and pre- and post-courier service implementation. A Root Cause Analysis was conducted to identify additional delays and opportunities for further optimization. Results: Between 2019 and 2022 median TAT was 22 days, with a downward trend in median TAT to 18.5 days at the end of 2022. Median OTS and TAT were significantly improved following courier service introduction (13 vs 7 days and 23 vs. 18.5 days, respectively). STR remained stable throughout the periods of interest. Only 63.6%-72.7% of clinicians reported correctly completing key steps of the ordering workflow possibly contributing to delays in OTS and TAT. Conclusions: We assessed the complex effort of optimizing the NGS testing workflow at a large safety-net health system. Courier service implementation improved OTS and overall TAT. Surveys identified inefficiencies in the provider side of the ordering process. Future opportunities to improve TAT include NGS order integration with electronic medical systems.